The effects of physical and hormonal treatments on dormancy breaking and the changes in seed coat ultrastructure of Delonix regia - SOLICHATUN SOLICHATUN; SANTOSA SANTOSA; KUMALA DEWI; RARASTOETI PRATIWI (Nusantara Bioscience, 2016)
Abstract. Solichatun, Santosa, Dewi K, Pratiwi R. 2016. The effects of physical and hormonal treatments on dormancy breaking and the changes in seed coat ultrastructure of Delonix regia. Nusantara Bioscience 8: 94-102. The seed dormancy is described as the inability of an intact viable seed to complete germination under favorable conditions. Delonix regia (Hook) Raf. also known as flamboyant is a member of Fabaceae that has seed dormancy. Every seed has a different structure in their seed coat that responsible for initiating imbibition of water due to dormancy breakdown and germination. The aims of this research were to investigate the effect of physical and hormonal treatment in dormancy break of flamboyant seed and to investigate the structure of seed coat on the dormancy and germination. The treatments were applied to break the dormancy of D. regia seeds were physical treatments and hormonal treatments (ABA, BAP, GA, and IBA). Morphological and anatomical changes during dormancy breakdown were investigated using scanning electron microscope. The imbibition pathway tracked using blocking experiment. The results indicated that physical treatment that seeds dipped in hot water (98oC) for 5 minutes was the most effective treatment to dormancy breakdown of flamboyant seeds (95%). The application of GA3 100 ppm results in the highest of germination percentage (22%) among other hormones. The result of blocking experiment showed that hilum and lens play an important role during imbibition processes; and the type of flamboyant seed water gap was the lens gap type.